Desiccation tolerance is associated with Staphylococcus aureus hypertransmissibility, resistance and infection development in the operating room. Issue 3 (November 2018) - Loftus, R.W.; Dexter, F.; Robinson, A.D.M.; Horswill, A.R.
Summary: Background: Desiccation tolerance increases Staphylococcus aureus survival and risk of transmission. A better understanding of factors driving intraoperative transmission of S. aureus pathogens may lead to innovative improvements in intraoperative infection control. Aims: To determine whether desiccation tolerance is associated with intraoperative S. aureus transmission, and to examine typical transmission dynamics for desiccation-tolerant isolates in the operating room in order to provide the impetus for development of improved intraoperative infection control strategies. Methods: S. aureus isolates ( N =173) were collected from anaesthesia work area reservoirs in 274 operating room environments. Desiccation tolerance was assessed and the potential association with sequence type (ST) and clonal transmission was evaluated. Whole cell genome analysis and pulsed-field gel electrophoresis analysis were used to compare desiccation-tolerant isolates with causative organisms of infection. Findings: S. aureus ST 5 isolates had greater desiccation tolerance than all other intraoperative STs [ST 5, N =34, median Day 2 colony-forming unit (cfu) survival 0.027% ± 0.029%; other STs, N =139, median Day 2 cfu survival 0.0091% ± 1.41%; corrected P =0.0001]. ST 5 was associated with increased risk of clonal transmission (relative risk 1.82, 95% confidence interval 1.23–2.71, P =0.003). ST 5 transmission was linked by whole cell genome analysis to postoperative infection. Conclusions: Increased desiccation tolerance is associated with intraoperative transmission of S. aureus ST 5 isolates that are linked to postoperative infection. Future work should determine whether attenuation of desiccation-tolerant, intraoperative ST 5 strains can impact the incidence of healthcare-associated infections.